Retention of the harpagoside content in dried Harpagophytum procumbens (Devil's Claw) root through controlled drying and the application of near infrared spectroscopy (NIRS) as rapid method of determination - Gray, Brian Robert (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc Food Sc )--Stellenbosch University, 2003.